Working Memory Capacity Fluid Intelligence are Strongly Related Constructs Comment on Acker , Beier, and Boyle (2005). [article]. - Kane, Michael J.
The authors agree with P. L. Ackerman, M. E. Beier and M. O. Boyle (2005) that working memory capacity (WMC) is not isomorphic with general fluid intelligence (Gf) or reasoning ability. However, the WMC and Gf/reasons are more strongly associated than Ackerman et al. (2005) indicate particularly when considering the outcomes of latent-variable studies. The authors reanalysis of 14 such date sets from 10 published studies, representing more than 3,100 young adult subjects, suggest a strong correlation between WMC and Gf reasoning factors (median r= .72), indicating that the WMC and Gf construct share approximately 50% of their variance. This comment also clarifies the authors " executive attention" view of WMC, it demonstrate that WMC has the greater discriminant validity than Ackerman et al. (2005) implied and its suggests some future directions and challenges for the scientific study of the convergence of WMC, attention control, and intelligence. -- (from the author).